International consensus guidelines on interventional endoscopy in chronic pancreatitis: recommendations from the working group for the international consensus guidelines for chronic pancreatitis in collaboration with the International Association of Pancreatology, the American Pancreatic Association, the Japan Pancreas Society, and European Pancreatic Club - Kitano, Masayuki; Gress, Thomas M.; Garg, Pramod K.; Itoi, Takao; Irisawa, Atsushi; Isayama, Hiroyuki; Kanno, Atsushi; Takase, Kei; Levy, Michael; Yasuda, Ichiro; Lévy, Phillipe; Isaji, Shuiji; et al. (Pancreatology, 2020)
Background/objectives - This paper is part of the international consensus guidelines on chronic pancreatitis, presenting for interventional endoscopy. - Methods - An international working group with experts on interventional endoscopy evaluated 26 statements generated from evidence on 9 clinically relevant questions. The Grading of Recommendations Assessment, Development, and Evaluation approach was used to evaluate the level of evidence. To determine the level of agreement, a nine-point Likert scale was used for voting on the statements. - Results - Strong consensus was obtained for 15 statements relating to nine questions including the recommendation that endoscopic intervention should be offered to patients with persistent severe pain but not to those without pain. Endoscopic decompression of the pancreatic duct could be used for immediate pain relief, and then offered surgery if this fails or needs repeated endoscopy. Endoscopic drainage is preferred for portal-splenic vein thrombosis and pancreatic fistula. A plastic stent should be placed and replaced 2-3 months later after insertion. Endoscopic extraction is indicated for stone fragments remaining after ESWL. Interventional treatment should be performed for symptomatic/complicated pancreatic pseudocysts. Endoscopic treatment is recommended for bile duct obstruction and afterwards surgery if this fails or needs repeated endoscopy. Surgery may be offered if there is significant calcification and/or mass of the pancreatic head. Percutaneous endovascular treatment is preferred for hemosuccus pancreaticus. Surgical treatment is recommended for duodenal stenosis due to chronic pancreatitis. - Conclusions - This international expert consensus guideline provides evidenced-based statements concerning indications and key aspects for interventional endoscopy in the management of patients with chronic pancreatitis.